Wildlife nursing - part two: an investigation into current challenges. Issue 1 (5th February 2021) - Varu, Jesle; Orpet, Hilary
ABSTRACT: British wildlife nursing is not included in the curricula for most training courses despite Registered Veterinary Nurses (RVNs) being expected to fulfil their professional, legal and ethical responsibilities in practice. These responsibilities should be considered to strike a balance between intervention and unnecessary suffering. As there is limited peer reviewed literature into veterinary interventions towards wildlife casualties, this descriptive and analytical study aimed to identify the major challenges Registered VNs (RVNs) and student VNs (SVNs) face when treating wildlife. Part two of this series of articles outlines the project carried out to gauge nursing competency, determine valuable education activities, and create a nursing model.